DIRETOR DE ESCOLA: GERENTE OU EDUCADOR? POSSIBILIDADES E LIMITAÇÕES DO DESENVOLVIMENTO DA FUNÇÃO PEDAGÓGICA EM UMA ESCOLA PÚBLICA ESTADUAL PAULISTA - Amaral, Izilda Castellani do (2008)
It has time, the difficulties faced for the directors of school of the state public net of São Paulo constitute reason of fidget and impotence, therefore these have its work plastered for the bureaucratic-administrative routine, which makes it difficult the performance of the pedagogical activities. This work centers in the study of the possibilities and limits in the development of the pedagogical function of the Director of School, by the way, Manager or Educator? In this research one uses documents of the Pertaining to school Unit, since its foundation in 1985 up to 2007, to understand the development of the function of school director, in this double bureaucraticadministrative and pedagogical aspect. In such a way, the following questions had been boarded: which are the requests and requirements of the State secretary of the Education of São Paulo (SEE-SP) and of the subordinated agencies it, in relation to the activities developed daily for the school director? Which the objective incumbencies that the school director has to answer for the SEE-SP? From this, which are the possibilities and the limits of the director to develop the pedagogical function in the pertaining to school environment? The given hypothesis is that, the school director does not obtain to center in the development of the pedagogical activities in face of the attendance to the bureaucratic-administrative requirements of the SEE-SP and the subordinated agencies it, which conditions its professional activity. It is intended with this study to contribute for the debate concerning the practical one of the pertaining to school management and the reflection of the functions and the paper of the director of school in the process of economicpolitician- social transformation. The presentation of this research is structuralized in three chapters. The end expositions point that the director of school, who has a great number of requests and requirements of bureaucratic-administrative tasks, emanated of the central power and its subordinated agencies, compromise the performance of the pedagogical functions.(AU)